Uranium decay daughters from isolated mines: Accumulation and sources. (November 2015) - Cuvier, A.; Panza, F.; Pourcelot, L.; Foissard, B.; Cagnat, X.; Prunier, J.; van Beek, P.; Souhaut, M.; Le Roux, G.
Abstract: This study combines in situ gamma spectrometry performed at different scales, in order to accurately locate the contamination pools, to identify the concerned radionuclides and to determine the distribution of the contaminants from soil to bearing phase scale. The potential mobility of several radionuclides is also evaluated using sequential extraction. Using this procedure, an accumulation area located downstream of a former French uranium mine and concentrating a significant fraction of radioactivity is highlighted. We report disequilibria in the U-decay chains, which are likely related to the processes implemented on the mining area. Coupling of mineralogical analyzes with sequential extraction allow us to highlight the presence of barium sulfate, which may be the carrier of the Ra-226 activities found in the residual phase (Ba(Ra)SO4 ). In contrast, uranium is essentially in the reducible fraction and potentially trapped in clay-iron coatings located on the surface of minerals. Graphical abstract: Highlights: A multistep methodology is followed to visualize the distribution of natural radionuclides around a closed uranium mine. Mobile gamma spectrometry quickly allows locating the main accumulation areas of U and decay products. The distribution of radionuclides is determined from kilometer to micrometer scale. A simple chemical extraction methodology is used to study the mobility of U and decay products. Two main sources of natural radionuclides are deduced from Ra-226/U-238 and Th-230/Ra-226 activity ratios.